Enhancing The Caliber of Learning Procedures and Results Via Strategic Program Assessment - Mahfudz Mahfudz (STAI Syaichona Moh. Cholil Bangkalan, 2024)
Evaluation is assessing student growth in the teaching and learning process. This article describes the strategic program evaluation method for improving the quality of learning processes and outcomes at Madrasah Aliyah Raudhatul Ulum, Lumajang Regency. This research uses a qualitative and descriptive method through a case study approach. Data collection in this research was interviews and direct observation in the field. The data analysis process involves phases of pattern matching, explanation building, time series analysis, logic model, and cross-case synthesis. The research found that evaluation forms include evaluating learning programs, learning outcomes, and learning processes. Evaluation aims to report student progress, inform the results achieved, maintain the results achieved, and make improvements in the learning process system.